Bentuk-Bentuk Pembinaan terhadap Lansia di UPT Pelayanan Sosial Anak dan Lanjut Usia di Siborong-Borong - Elia Silalahi; Risma Sipahutar; Ria Surbakti; Maya Sianturi; Mawar Silalahi; Amelia Pakpahan; Helma Purba; Sara Nasution; Gomgom Sianipar; Damayanti Nababan (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this article is to determine the forms of leadership in the elderly. The elderly group is the last stage of maturity in a person's life, which requires some kind of Christian education or church teachings, but not everyone reaches that age, so this age is often called the golden age. Most people think they don't need special education as they get older. What is meant by elderly is a person who has reached the age of 60 years and whose physical strength has weakened to such an extent that they are no longer able to earn a living. their strength or endurance and work are already limited. Spiritual formation for the elderly is very necessary to strengthen the faith of the elderly in their old age, whose physical abilities are increasingly decreasing, causing many problems for the elderly. Therefore, by using qualitative methods and a literary approach it can be concluded that the forms of spiritual education given to the elderly are: visits to nursing homes, counseling, worship/fellowship for the elderly, catechism before death, visits to nursing homes. leading prayer and meditation, involving the elderly in services and helping the elderly when they are sick. That's what coaches really need to give to seniors.